Diseño de una propuesta para el mejoramiento del proceso de preparación y despacho de repuestos en la empresa Indufrial s.a planta Cartagena (2021)
This research is carried out to design a proposal to the company Indufrial S.A in the Cartagena plant in view of the need that arises to improve the process of preparation and dispatch of spare parts. With this project, improvements will be suggested for the management of materials dispatch, in order to have greater control in the process. To comply with this, first a diagnosis of the procedures carried out will be carried out using tools such as the study of time and movement of the process, conducting interviews and a checklist, which will allow to know its operation, identification of shortcomings and generation of improvement opportunities. A strategy for the distribution of the spaces used in carrying out the preparation, packing and packing activities will be proposed in order to argue that the employees are currently not adequate and a proposal will be presented with evidence and cost evaluation for its adequacy. Finally, a system of indicators is proposed that contributes to the monitoring of compliance with the aforementioned.